Inventing the Reinvention? Tradition and the Body of Dancing Women - Yusti Dwi Nurwendah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
The practice of dance has historically been associated with complex social and political functions. There is abundant evidence demonstrating dance’s centrality in society, and it has become an integral part of the historical process. Concurrently, dance becomes an identity associated with women. In line with Hobsbawm’s concept of the invention of tradition. This study investigates the Jathilan Obyog tradition in Ponorogo through the lens of Hobsbawm’s notion of the invention of tradition, focusing on the dominant elite and the participation of Jathil women. The present study employs a qualitative approach, specifically utilizing ethnographic methodology. The data were collected through participant observation, interviews, and documentation that were tailored to the specific context and research objectives. The investigation employed the notion of the fabrication of tradition, initially introduced by Eric Hobsbawm and Terence Ranger, as the focal point of examination. The result shows that in a hegemonic endeavor that attempts to ‘discipline’ the tradition, Jathil women have succeeded in determining the power to reinvent tradition in picturesque ways, primarily through the body and with massive media support to create the process of reconstructing social memory and imagination. This research brings positive views of women as cultural agents within society.